STUDI KORELASI FASILITAS BELAJAR DI RUMAH DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR GEOGRAFI PADA SISWA KELAS XI - Elvia Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the relationship between home learning facilities and learning motivation on geography learning outcomes of eleventh-grade students at SMA Negeri 1 Kepenuhan, Rokan Hulu Regency. This research employed a quantitative approach with a correlational method. The population of this study consisted of all eleventh-grade students, while the sample was determined using an appropriate sampling technique. Data were collected through questionnaires to measure home learning facilities and learning motivation, as well as documentation of students’ geography achievement scores to obtain learning outcome data. The data analysis techniques included prerequisite tests (normality and linearity tests) and hypothesis testing using correlation and regression analysis. The results revealed that there was a positive and significant relationship between home learning facilities and students’ geography learning outcomes. In addition, learning motivation also showed a positive and significant relationship with geography learning outcomes. Simultaneously, home learning facilities and learning motivation contributed to the improvement of students’ geography learning outcomes. These findings indicate that adequate home learning facilities and high learning motivation play an important role in supporting students’ academic success, particularly in geography learning. Therefore, collaboration among schools, parents, and students is essential to create a conducive learning environment that enhances optimal learning outcomes.